Unique datasets on shocks, food security, and household coping strategies: Creating new analytical playgrounds to study coping behavior in the multi-shock environments of Mali, Chad, Niger, and Burkina Faso (2018-2023) - Marivoet, Wim; Sib, Ollo; Samake, Aliou Badara; Dieme, Ndeye Fatou; Hema, Aboubacar; Doehnert, Federico; Suzuki, Mina (International Food Policy Research Institute, 2025)
To inform the Cadre Harmonisé process in West Africa, large-scale national household surveys are usually implemented twice a year to capture data on household food security and several forms of consumption- and livelihood-based coping strategies. These cross-sectional surveys typically take place around February-March (before the start of the lean season) and September-October (at the end of the lean season or beginning of the harvesting period), and they are generally representative at the second-tier administrative level. Despite their different names (that is, ENSAN in Mali, ENSA in Chad, EVIAM in Niger, and ENISAN in Burkina Faso) and the methodological revisions introduced over the years, these surveys have a large common set of variables that were pooled together by standardizing the modalities of all common variables found across the multiple survey waves between 2018 and 2023. Apart from reconsolidation and reprocessing of initial data files, this process also involved the re-computation of several key indicators on food security and household coping as to assure maximum methodological consistency over time.